Bats of the Vietnamese Mekong Delta: A revised checklist with significant new records - Tu, Vuong Tan; Furey, Neil M.; Koyabu, Daisuke; Arai, Satoru; Görföl, Tamás; Ngon, Lam Quang; Nojiri, Taro; Fukui, Dai; Csorba, Gábor; Balvín, Ondřej; Tuan, Le Quang; Tuan, Tran Anh; et al. (Zootaxa, 2026)
We present updated baseline information on bats inhabiting the Vietnamese Mekong Delta based on literature review and field expeditions between 2018 and 2024. In total, 32 bat species from six families were documented across 23 study sites within the delta. Our integrated analyses of morphological and acoustic data along with mitochondrial sequences reveal two new country records (Rhinolophus thailandensis and Hipposideros kingstonae) and novel populations of relict forms in several species’ complexes (R. macrotis, R. marshalli, and H. galeritus). These findings indicate that bat populations in the Vietnamese Mekong Delta include previously undocumented diversity and unique evolutionary patterns. However, bats and other wildlife within the delta face escalating threats from the synergistic effects of anthropogenic activities (e.g., unsustainable land-use and farming practices, illegal hunting, wind energy development) and climate change. Compounding these threats, public awareness of the importance of bat conservation remains limited and misperceptions of bats as sources of zoonotic diseases remains widespread. We advocate for urgent implementation of multidisciplinary initiatives to conserve the unique biodiversity of the Vietnamese Mekong Delta and achieve sustainable development goals.